Efforts to increase the group of teacher competency through the teacher work groups in central bakung cimahi - Syah Khalif Alam (IKIP Siliwangi Bandung, 2018)
EFFORTS TO INCREASE THE TEACHER'S GROUP TEACHER COMPETENCY THROUGH THE TEACHER WORK GROUPS IN CENTRAL BAKUNG CIMAHI Syah Khalif Alamradityaalief@gmail.comIKIP Siliwangi AbstractThis study aims to determine the implementation process and the results of teacher competency development in the group of teachers of the kindergarten cluster Bakung Cimahi Tengah. The formulation of the problem in this research is whether the teacher working group can improve the competence of kindergarten teacher group in Central Cimahi? And how the implementation process, the results of coaching, advantages, and disadvantages after the guidance of pedagogic competence of teachers in the cluster group of teachers Cilahi Tengah. The approach used in this research is qualitative approach with descriptive research method. The population in this research is in Cimahi Tengah lily group consisting of 29 teachers from 7 kindergarten schools. Based on the results of research that during the process of implementation of the working group of teachers still do not understand its role as a subject of learning. While the result of guidance pedagogic competence of teachers successfully implemented, the teacher showed an active, enthusiastic, and happy attitude during the learning took place. It can be concluded that improving the competence of teachers through teacher workgroups can experience a significant increase as when supervisors provide direction and guidance look more active and confident, and improve the competence of teachers through teacher work groups more effectively and better, teachers are more understanding and can doing activities well. Key Words: Teacher Competence, Early Childhood Education, Teacher Working Groups